PIXE and RES as a tool for the analysis of historic copper halfpennies - Abraham, M; Grime, G; Northover, J; Smith, C (1999)
RES and PIXE microbeam analysis is used to investigate the trace element concentrations as well as the surface corrosion of counterfeited copper halfpennies from the mid 18th century. PIXE elemental mapping was used to identify regions with a minimum of light element contamination which could be used for accurate trace element determinations. RES analysis of selected points on the map could be used to confirm the absence of corrosion or contamination, and in addition yielded valuable information on the composition and structure of the corrosion layers. (C) 1999 Elsevier Science B.V. All rights reserved.